Decreased compliance in the deep and superficial conduit veins of the upper arm during prolonged cycling exercise. Issue 8 (24th April 2017) - Oue, Anna; Sato, Kohei; Yoneya, Marina; Sadamoto, Tomoko
Abstract: We examined whether there is a difference in compliance between the deep and superficial conduit veins of the upper arm in response to prolonged exercise. Eight young men performed cycling exercise at 60% of peak oxygen uptake until rectal temperature had been increased by 1.1°C for 38–48 min. The cross‐sectional area (CSA) of the brachial (deep) and basilic (superficial) veins was assessed by ultrasound during a cuff deflation protocol. Compliance (CPL) was calculated as the numerical derivative of the cuff pressure and CSA curve. During prolonged exercise, CPL in both conduit veins was similarly decreased when compared with pre‐exercise values; however, the CSA decreased in the deep vein but increased in the superficial vein. In addition, passive heating caused an analogous change in CSA and CPL of superficial vein when compared with prolonged exercise, but did not change CSA and CPL of deep vein. Cold pressor test induced the decreased CSA of deep and superficial veins without the alteration of CPL of both veins. These results suggest that CPL in the deep and superficial conduit veins adjusts to prolonged exercise via different mechanisms. Abstract : Compliance in the deep and superficial conduit veins were similarly reduced during prolonged exercise in spite of opposite cross‐sectional area of vein responses. The reduction in compliance in the deep vein was mediated by active venoconstriction while that in the superficial vein was by passive dilation of the vessel due to increased blood flow.